Urgensi Pembelajaran IPS pada Materi Konsep Uang Digital untuk Siswa SD - Maylitha, Evi; Galand, Patricia Bunga Juwita; Hikmah, Shofi Nurul; Rustini, Tin (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the development of money in the world where money is currently found in digital form. The concept of money is one of the social science learning materials in elementary schools. Learning the concept of money aims to introduce the development of money used in everyday life. Money concept material needs to be taught to students to increase understanding and develop character related to financial intelligence. This research aims to determine the importance of social studies learning on digital money concept material for elementary school students. This research is qualitative research with the type of library study. Data is obtained from research results contained in journals, articles, theses and theses. Data analysis is carried out by collecting data, presenting it and also drawing conclusions. The results of this research show that social studies learning plays an important role in introducing the concept of digital money to students through TPACK